Gambaran Ibu yang Memijatkan Bayi ke Dukun Bayi di Desa Jambu Kabupaten Semarang - Yola Sartika; Ninik Christiani, S.Si T., M.Kes; Moneca Diah L (Journal of Holistics and Health Science, 2021)
Baby massage is a direct contact therapy with the body that can provide a sense of security and comfort for babies. The villagers chose to use a shaman as an alternative to baby massage on the grounds that it is affordable and saves time because the shaman can do baby massage at home. To find out the picture of a mother massaging a baby to a shaman in Jambu Village, Semarang Regency. Method : This research is quantitative descriptive. The population in this study were 20 mothers who had babies in Jambu Village. The sample of this study was 20 mothers who had babies. Purposive sampling technique. The instrument uses a questionnaire. Analysis uses frequency distribution and percentage. Most of the education level of mothers who massaged infants to traditional birth attendants in Jambu Village were 12 respondents (60.0%) of SMK / SMA. The culture of mothers who massage infants into traditional birth attendants in Jambu Village, does not support as many as 10 respondents (50.0%). Most of the economy of mothers who massaged infants to traditional birth attendants in Jambu Village, â‰¥ UMR (Rp. 2,055,000) were 14 respondents (70.0%). Most of the support from the mother's family to massage the baby to the shaman in Jambu Village, as many as 13 respondents (65.5%). Mothers should massage their baby to health workers who know the anatomy of the correct massage physiology or skilled shaman and have received training from health workers on proper baby massage and do not harm the baby. ABSTRAK Pijat bayi merupakan terapi sentuh kontak langsung dengan tubuh yang dapat memberikan rasa aman dan nyaman pada bayi. Masyarakat desa memilih dukun bayi sebagai alternatif untuk pijat bayi dengan alasan biaya yang terjangkau dan menghemat waktu karena dukun bayi dapat melakukan pijat bayi dirumah. Untuk mengetahui gambaran ibu yang memijatkan bayi ke dukun bayi di Desa Jambu, Kabupaten Semarang. Penelitian ini bersifat deskriptif kuantitatif. Populasi dalam penelitian ini 20 orang ibu yang memiliki bayi di Desa Jambu. Sampel penelitian ini20 orang ibu yang memiliki bayi. Teknik sampling purposivesampling. Instrumen menggunakan kuesioner. Analisis data menggunakan distribusi frekuensi dan presentase. Sebagian besar tingkat pendidikan ibu yang memijatkan bayi ke dukun bayi di Desa Jambu, adalah SMK/SMA sebanyak 12 responden (60,0%). Kebudayaan ibu yang memijatkan bayi ke dukun bayi di Desa Jambu,tidak mendukung sebanyak 10 responden (50,0%). Sebagian besar ekonomi ibu yang memijatkan bayi ke dukun bayi di Desa Jambu, â‰¥ UMR (Rp. 2.055.000) sebanyak 14 responden (70,0%). Sebagian besar dukungan keluarga ibu untuk memijatkan bayi ke dukun bayi di Desa Jambu,sebanyak 13 responden (65,5%). Ibu diharapkan memijatkan bayinya ke tenaga kesehatan yang mengetahui anatomi fisiologi pemijatan yang benar atau dukun yang terampil dan telah mendapatkan pelatihan dari tenaga kesehatan tentang pijat bayi yang benar dan tidak membahayakan bayi.